Adhesive composition and connection structure

KR103022650B1Active Publication Date: 2026-09-18RESONAC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020227036120
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2021-02-17
Publication Date
2026-09-18
Estimated Expiration
2041-02-17

Smart Images

  • Figure 112022109385217-PCT00002_ABST
    Figure 112022109385217-PCT00002_ABST
Patent Text Reader

Abstract

One aspect of the present invention is a connection structure comprising a first circuit member having a first electrode, a second circuit member having a second electrode, and a connection portion installed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein at least one of the first electrode and the second electrode has a layer formed of Cu or Ag on its outermost surface, and the connection portion has a layer formed of Pd or Au on its outermost surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an adhesive composition and a connection structure. Background Technology

[0002] Recently, electronic components have been miniaturized, thinned, and improved in performance, and along with this, the development of high-density packaging technology is actively underway. In such high-density packaging, it is difficult to connect circuit components having microcircuit electrodes using conventional solder and rubber connectors. Therefore, various connection methods using anisotropic conductive adhesives and films with excellent resolution are being used. In this connection method, for example, when connecting a flexible printed circuit board (FPC) to a glass substrate of a liquid crystal display, an anisotropic conductive adhesive film containing conductive particles is placed between opposing electrodes, and by heating and pressing, the circuit components are bonded and fixed together, while maintaining insulation between adjacent electrodes on the same circuit component, and the electrodes of the two circuit components are electrically connected.

[0003] As a conductive particle used in an anisotropic conductive adhesive as described above, for example, Patent Document 1 discloses a conductive particle having a metal layer formed on the surface of a particle to be formed, wherein the Vickers hardness (Hv) of the metal layer is 35 or higher and 400 or lower, and the thickness of the metal layer is 5 nm or higher and 250 nm or lower. The metal layer formed on the surface of this conductive particle is composed of at least one metal material selected from the group consisting of copper (Cu), aluminum (Al), nickel (Ni), titanium (Ti), and ruthenium (Ru). Prior art literature

[0004] Japanese Patent Publication No. 2016-181511 The problem to be solved

[0005] However, according to the inventors' review, when the outermost surface of the electrode to be connected is composed of a layer formed of Cu or Ag, it was found that even if an adhesive containing conductive particles as disclosed in Patent Document 1 is used, a good connection is obtained at the beginning of the connection, but the connection cannot be maintained over a long period of time (the reliability of the connection becomes insufficient).

[0006] Accordingly, the objective of the present invention is to obtain a more reliable electrical connection when a circuit member having an electrode formed of Cu or Ag on its outermost surface is connected by an adhesive containing conductive particles. means of solving the problem

[0007] One aspect of the present invention is a connection structure comprising a first circuit member having a first electrode, a second circuit member having a second electrode, and a connection portion installed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein at least one of the first electrode and the second electrode has a layer formed of Cu or Ag on its outermost surface, and the connection portion has a layer formed of Pd or Au on its outermost surface.

[0008] Another aspect of the present invention is an adhesive composition containing an adhesive component and conductive particles, used to electrically connect a first circuit member having a first electrode and a second circuit member having a second electrode by bonding them together, wherein the conductive particles have a layer formed of Pd or Au on the outermost surface and at least one of the first electrode and the second electrode has a layer formed of Cu or Ag on the outermost surface.

[0009] In each of the above aspects, the conductive particle may have a layer formed of Pd on its outermost surface. Effects of the invention

[0010] According to the present invention, when a circuit member having an electrode formed of Cu or Ag on its outermost surface is connected by an adhesive containing conductive particles, a more reliable electrical connection can be obtained. Brief explanation of the drawing

[0011] FIG. 1 is a cross-sectional view schematically illustrating one embodiment of an adhesive composition. FIG. 2 is a cross-sectional view schematically illustrating one embodiment of a conductive particle. FIG. 3 is a cross-sectional view schematically illustrating one embodiment of a method for manufacturing a connection structure. Specific details for implementing the invention

[0012] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings as applicable. Furthermore, in this specification, numerical ranges indicated by "to" represent a range that includes the values ​​described before and after "to" as minimum and maximum values, respectively. Additionally, individually described upper and lower limits may be combined arbitrarily. Furthermore, in this specification, "(meth)acrylate" refers to at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl." However, the present invention is not limited to the following embodiments.

[0013] The adhesive composition according to one embodiment is an adhesive film formed in a film shape. In another embodiment, the adhesive composition may be in a state other than a film shape (e.g., a paste).

[0014] FIG. 1 is a cross-sectional view schematically illustrating a film-shaped adhesive composition (adhesive film) according to one embodiment. As shown in FIG. 1, the adhesive film (1) comprises, in one embodiment, an adhesive component (2) and conductive particles (3) dispersed in the adhesive component (2). The thickness of the adhesive film (1) may be, for example, 10 μm or more, or 50 μm or less.

[0015] In one embodiment, the adhesive component (2) contains a curable component that has insulating properties and is cured by heat or light. The adhesive component (2) is defined as a component other than the conductive particles in the adhesive composition.

[0016] The curable component may include a polymerizable compound and a polymerization initiator, may include a thermosetting resin, or may include a polymerizable compound, a polymerization initiator, and a thermosetting resin.

[0017] The polymerizable compound may be, for example, a radical polymerizable compound. A radical polymerizable compound is a compound having a functional group that polymerizes by radicals. Examples of radical polymerizable compounds include (meth)acrylate compounds and maleimide compounds. The polymerizable compound may be used alone or in combination of two or more types. The content of the polymerizable compound may be, for example, 50 mass% or more and 80 mass% or less, based on the total amount of the adhesive components.

[0018] (Meth)acrylate compounds include, for example, urethane (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dimethylol tricyclodecane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, 2-hydroxy-1,3-di(meth)acryloxypropane, 2,2-bis[4-((meth)acryloxymethoxy)phenyl]propane, 2,2-bis[4-((meth)acryloxypolyethoxy)phenyl]propane, Examples include dicyclopentenyl (meth)acrylate, tricyclodecanyl (meth)acrylate, bis((meth)acryloxyethyl)isocyanurate, ε-caprolactone modified tris((meth)acryloxyethyl)isocyanurate, tris((meth)acryloxyethyl)isocyanurate, 2-(meth)acryloyloxyethyl acid phosphate, etc. From the perspective of adhesion, radical polymerizable compounds may include urethane (meth)acrylates.

[0019] The viscosity of the polymerizable compound at 25°C may be 100,000 mPa·s or higher, 100,000 mPa·s or lower, or 500,000 mPa·s or lower. The viscosity of the polymerizable compound can be measured using a commercially available E-type viscometer.

[0020] The polymerization initiator may be, for example, a radical polymerization initiator. The radical polymerization initiator is a compound that decomposes upon heating or light to generate free radicals, for example, a peroxide compound or an azo compound. The polymerization initiator is appropriately selected based on the desired connection temperature, connection time, working time, etc. The content of the polymerization initiator may be, for example, 0.05 mass% or more and 15 mass% or less, based on the total amount of the adhesive components.

[0021] The radical polymerization initiator may be one or more selected from, for example, benzoyl peroxide, diacyl peroxide, peroxydicarbonate, peroxy ester, peroxy ketal, dialkyl peroxide, and hydroperoxide. The radical polymerization initiator may be an organic peroxide having a half-life of 10 hours at a temperature of 40°C or higher and a half-life of 1 minute at a temperature of 180°C or lower, in terms of high reactivity and available time. The radical polymerization initiator may be used in combination with decomposition accelerators, inhibitors, etc. The polymerization initiator is used as a single type or in combination of two or more types.

[0022] Examples of thermosetting resins include epoxy resin, cyanate ester resin, maleimide resin, allylnadiimide resin, phenol resin, urea resin, melamine resin, alkyd resin, acrylic resin, unsaturated polyester resin, diallyl phthalate resin, silicone resin, resorcinol formaldehyde resin, xylene resin, furan resin, polyurethane resin, ketone resin, trialyl cyanurate resin, polyisocyanate resin, resin containing tris(2-hydroxyethyl)isocyanurate, resin containing trialyl trimellitate, thermosetting resin synthesized from cyclopentadiene, and thermosetting resin obtained by the trimerization of aromatic dicyanamide. Thermosetting resins are used either alone or in combination of two or more types. The content of the thermosetting resin may be, for example, 20 mass% or more or 50 mass% or less, based on the total amount of the adhesive components.

[0023] When the adhesive component contains a thermosetting resin, the adhesive component may further contain a curing agent. The curing agent may be melamine and its derivatives, hydrazide-based curing agents, boron trifluoride-amine complexes, sulfonium salts, amine imides, diaminomaleonitrile, polyamine salts, dicyandiamides, etc., or modified products thereof. The curing agent may be a medium-addition type curing agent such as polyamine, polymericaptan, polyphenol, or acid anhydride, or a combination of a medium-addition type curing agent and a catalytic type curing agent may be used. The curing agent may be used alone or in combination of two or more types. The content of the curing agent may be, for example, 0.5 mass% or more and 15 mass% or less, based on the total amount of the adhesive component.

[0024] The adhesive component may further include a polymerization inhibitor. The polymerization inhibitor may be hydroquinone, methyl ether hydroquinone, etc. The content of the polymerization inhibitor may be, for example, 0.05 mass% or more and 5 mass% or less, based on the total amount of the adhesive component.

[0025] The adhesive components may further contain fillers such as silica particles, softeners, accelerators, anti-aging agents, coloring agents, flame retardants, thixotropic agents, coupling agents, etc.

[0026] When forming an adhesive composition into a film shape, the adhesive component may further include a thermoplastic resin to improve film formation ability. Examples of thermoplastic resins include polystyrene, polyethylene, polyvinyl butyral, polyvinyl formal, polyimide, polyamide, polyester, polyvinyl chloride, polyphenylene oxide, urea resin, melamine resin, phenolic resin, xylene resin, epoxy resin, polyisocyanate resin, phenoxy resin, polyimide resin, polyester urethane resin, polyurethane resin, etc.

[0027] The thermoplastic resin is preferably an epoxy resin or a phenoxy resin, and for the purpose of further increasing connection reliability, it may be an epoxy resin or a phenoxy resin with a weight average molecular weight of 10,000 or more obtained from high-speed liquid chromatography (HPLC). The adhesive component may contain a resin in which these resins are modified at radical polymerizable functional groups. In addition to these resins, the adhesive component may contain a styrene-based resin or an acrylic resin for the purpose of adjusting melt viscosity, etc.

[0028] FIG. 2 is a cross-sectional view schematically illustrating one embodiment of a conductive particle (3) included in an adhesive film (1). As shown in FIG. 2(a), the conductive particle (3A) according to one embodiment has a polymer particle (31) that is approximately spherical in shape, a first metal layer (32A) installed on the polymer particle (31), and a second metal layer (33A) installed on the first metal layer (32A). The conductive particle (3A) may be approximately spherical in shape. It is preferable that substantially the entire surface of the polymer particle (31) be covered with the first metal layer (32A) and the second metal layer (33A), but a portion of the surface of the polymer particle (31) may be exposed without being covered with the first metal layer (32A) and the second metal layer (33A) to maintain the function of electrically connecting circuit members.

[0029] The polymer particles (31) may be particles comprising a polymer comprising, for example, at least one monomer selected from styrene and divinylbenzene as a monomer unit. The polymer may further comprise (meth)acrylate as a monomer unit.

[0030] The average particle size (diameter) of the polymer particles (31) may preferably be 1 μm or more, or 40 μm or less. From the perspective of high-density packaging, the average particle size (diameter) of the polymer particles (31) may more preferably be 1 μm or more, or 30 μm or less. From the perspective of maintaining a more stable connection state when there is a deviation in the unevenness of the electrode surface, the average particle size (diameter) of the polymer particles (31) may more preferably be 2 μm or more, or 20 μm or less.

[0031] The first metal layer (32A) is formed of, for example, Ni, Cu, NiB, Ag, or Ru, and preferably formed of Ni. The thickness of the first metal layer (32A) may be, for example, 50 nm or more, or 300 nm or less.

[0032] The second metal layer (33A) is formed of Pd or Au, and is preferably formed of Pd to further improve connection reliability. That is, the conductive particle (3A) has a layer formed of Au or Pd on the outermost surface of the conductive particle (3A), and is preferably formed of Pd to further improve reliability. The thickness of the second metal layer (33A) may be, for example, 2 nm or more, 5 nm or more, or 10 nm or more, or 200 nm or less, 100 nm or less, or 50 nm or less.

[0033] The average particle size (diameter) of the conductive particles (3A) may preferably be 1 μm or more, or 100 μm or less. From the perspective of high-density mounting, the average particle size (diameter) of the conductive particles (3A) may more preferably be 50 μm or less. From the perspective of maintaining a more stable connection state when there is a deviation in the irregularity of the electrode surface, the average particle size (diameter) of the conductive particles (3A) may more preferably be 2 μm or more or 3 μm or more, or 30 μm or less or 20 μm or less.

[0034] In this specification, the average particle size of the polymer particles and the average particle size of the conductive particles are each defined as the average value of the particle sizes obtained by measuring the particle size (diameter) of 300 polymer particles and 300 conductive particles in the adhesive composition using a scanning electron microscope (SEM).

[0035] The thickness of the first metal layer (32A) and the second metal layer (33A) each refers to the thickness in the portion of the metal layer where the protrusions described later are not formed. The thickness of the first metal layer (32A) and the second metal layer (33A) each is defined as the average value of the thicknesses obtained by measuring the thickness of the first metal layer and the second metal layer by observation using a scanning electron microscope (SEM) for 300 conductive particles in the adhesive composition.

[0036] In another embodiment, protrusions may be formed on the surface of the conductive particle (3). As shown in FIG. 2(b), the conductive particle (3B) according to another embodiment has a polymer particle (31) that is roughly spherical in shape, a first metal layer (32B) installed on the polymer particle (31), and a second metal layer (33B) installed on the first metal layer (32B), and a plurality of protrusions (34) are formed on the surface of the conductive particle (3B). The conductive particle (3B) will be described below, but since the conductive particle (3B) is common to the conductive particle (3A) shown in FIG. 2(a) except for the fact that it has protrusions (34), the description of the common configuration will be omitted.

[0037] In the conductive particle (3B), the protrusion (34) is composed of a first metal layer (32B) and a second metal layer (33B). The height of the protrusion (34) is preferably 60 nm or more, 90 nm or more, or 100 nm or more in order to further improve connection reliability, and preferably 1200 nm or less, 600 nm or less, 400 nm or less, or 200 nm or less.

[0038] Here, the height of the protrusion (34) is determined by analyzing a two-dimensional image containing a projected image of a conductive particle. The analysis of the two-dimensional image can be performed according to the method described in Japanese Patent Publication No. 2016-61722.

[0039] Specifically, the height of the protrusion can be determined by a method comprising: a process of detecting a particle edge, which is the boundary between the projected image of each conductive particle and other regions in a two-dimensional image in which a plurality of conductive particles are captured, for example; a process of calculating the center coordinates of the conductive particles in the two-dimensional image based on the particle edge; a process of dividing the particle edge into a plurality of particle edge parts (e.g., 12) for every predetermined angle around the center coordinate, calculating the difference between the maximum and minimum values ​​of the distance between the center coordinate and the particle edge for each of the plurality of particle edge parts, and calculating the average value of the difference as the height of the protrusion; and a process of calculating the average value of the calculated height of the protrusion for a plurality of conductive particles (e.g., any number from 5 to 100).

[0040] In the analysis of the above two-dimensional image, the particle edge substantially corresponds to the outer periphery containing irregularities originating from protrusions on the two-dimensional projection of the conductive particle. The frequency distribution of luminance obtained from the two-dimensional image generally exhibits a minimum value reflecting the particle edge portion. The two-dimensional image is binarized using the luminance corresponding to this minimum value as the first threshold to generate a binarized image. The edge formed in the obtained binarized image is detected as a particle edge. Based on the particle edge, the center coordinates of the conductive particle on the two-dimensional image are calculated. A circle fitting the particle edge is obtained using the least squares method, and the center of that circle becomes the center coordinates of the conductive particle.

[0041] The area ratio of the protrusion (34) to the entire surface projection of the conductive particle (3) (area ratio of the protrusion (34)) is preferably 8% or more, 9% or more, 10% or more, or 20% or more in terms of further improving connection reliability, and preferably 60% or less or 50% or less.

[0042] The area ratio of the protrusion can also be determined by analyzing a two-dimensional image of a conductive particle according to the method described in Japanese Patent Publication No. 2016-61722. The area ratio of the protrusion can be determined by a method comprising, for example, a process of calculating a second threshold corresponding to the boundary between the protrusion and the other part from the frequency distribution of luminance in the inner region of the particle edge, a process of binarizing the inner region of the particle edge by the obtained second threshold to generate a binarized image, and a process of calculating the area ratio of the region corresponding to the protrusion to the inner region of the particle edge in the obtained binarized image as the area ratio of the protrusion.

[0043] As described above, the conductive particle (3) can be obtained by forming a first metal layer (32) and a second metal layer (33) by metal plating on the surface of, for example, a polymer particle (31). More specifically, for example, after forming the first metal layer (32) by metal plating on the surface of, for example, a polymer particle (31), the second metal layer (33) can be obtained by forming an Au or Pd layer by substitution plating.

[0044] When producing the conductive particles (3B) shown in FIG. 2(b), the protrusions (34) can be formed by changing the plating conditions during metal plating to change the thickness of the first metal layer (32) and the second metal layer (33). More specifically, for example, the protrusions (34) can be formed by gradually increasing the concentration of the plating solution during the metal plating process.

[0045] As the conductive particle (3) described above has a second metal layer (33) formed of Pd or Au on its outermost surface, it is possible to obtain a more reliable electrical connection when using an adhesive composition (adhesive film (1)) containing the conductive particle (3) to connect a circuit member (details to be described later) having a layer formed of Cu or Ag on its outermost surface, which is the electrode to be connected.

[0046] The content of conductive particles (3) included in the adhesive film (1) is determined according to the fineness of the electrode to be connected, etc. For example, the content of conductive particles (3) may be 1 part by mass or more, or 200 parts by mass or less, with respect to 100 parts by mass of the adhesive component, and preferably 100 parts by mass or less, or 50 parts by mass or less, from the perspective of insulation and manufacturing cost.

[0047] The adhesive composition may contain only the conductive particles (3) described above as conductive particles, or may further contain conductive particles other than the conductive particles (3) described above (hereinafter also referred to as "other conductive particles"). The other conductive particles may be, for example, conductive particles in a dendrite shape (also called resin shape). The dendrite-shaped conductive particles have one main axis and a plurality of branches branching out two-dimensionally or three-dimensionally from the main axis. The dendrite-shaped conductive particles may be formed of a metal such as copper or silver, or, for example, silver-coated copper particles formed by copper particles being coated with silver.

[0048] Dendrite-shaped conductive particles are available, specifically, as ACBY-2 (Mitsui Metal Mining Co., Ltd.), CE-1110 (Fukuda Metal Foil Powder Co., Ltd.), #FSP (JX Metal Co., Ltd.), and #51-R (JX Metal Co., Ltd.). Alternatively, dendrite-shaped conductive particles can also be manufactured by known methods (e.g., the method described in International Publication No. 2014 / 021037).

[0049] Other conductive particles may include, in addition to dendrite-shaped conductive particles, needle-shaped conductive particles (e.g., needle-shaped conductive particles coated with silver on potassium titanate fibers, available as YTA-1575 (YCC Yokozawa Metal Industry Co., Ltd.)), amorphous conductive particles (e.g., amorphous conductive particles coated with copper on graphite, available as CC-13D (YCC Yokozawa Metal Industry Co., Ltd.)), etc.

[0050] The content of other conductive particles may be, for example, 5 parts by mass or more, or 100 parts by mass or less, per 100 parts by mass of the adhesive component.

[0051] The adhesive composition may be in the form of a multilayer film (multilayer adhesive film). The multilayer adhesive film may be composed of two layers, for example, a layer containing conductive particles and a layer not containing conductive particles, or it may be composed of three layers, a layer containing conductive particles and layers not containing conductive particles installed on both sides thereof. The multilayer adhesive film may have multiple layers containing conductive particles. Considering adhesion to circuit members, the multilayer adhesive film may have an adhesive layer that exhibits high adhesion to the circuit member to be connected. When this multilayer adhesive film is used, conductive particles can be efficiently captured on the connection electrode, which is advantageous for connecting circuit members with a narrow pitch.

[0052] The adhesive composition (adhesive film) described above is suitably used as a material (circuit connection material) for connecting circuit members together, and more specifically, is particularly suitably used as an anisotropic conductive adhesive composition (anisotropic conductive adhesive film) or an isotropic conductive adhesive composition (isotropic conductive adhesive film) for connecting circuit members together.

[0053] Next, a method for manufacturing a connection structure using an adhesive film (1) is described. FIG. 3 is a cross-sectional view schematically illustrating a method for manufacturing a connection structure according to one embodiment. First, as shown in FIG. 3 (a), a first circuit member (4), a second circuit member (5), and an adhesive film (1) (circuit connection material) are prepared. The first circuit member (4) has a first substrate (6) and a first electrode (7) installed on one surface (6a) of the first substrate (6). The second circuit member (5) has a second substrate (8) and a second electrode (9) installed on one surface (8a) of the second substrate (8).

[0054] Next, the first circuit member (4) and the second circuit member (5) are arranged so that the first electrode (7) and the second electrode (9) face each other, and an adhesive film (1) is placed between the first circuit member (4) and the second circuit member (5) to produce a laminate.

[0055] Then, the adhesive film (1) is cured while applying pressure to the entire laminate in the direction indicated by the arrow in FIG. 3 (a). The pressure applied during the application may be, for example, 1 to 10 MPa per total contact area. The method of curing the adhesive film (1) may be by heating, or by using light irradiation in addition to heating. Heating may be performed at, for example, 100 to 170°C. The application of pressure and heating (light irradiation if necessary) may be performed for, for example, 1 to 160 seconds. By doing so, the first circuit member (4) and the second circuit member (5) are compressed through the cured adhesive composition constituting the adhesive film (1).

[0056] In the above embodiment, an adhesive film (1) is placed between the first circuit member (4) and the second circuit member (5), but in another embodiment, instead of an adhesive film, a paste-like adhesive composition may be applied to one or both of the first circuit member (4) and the second circuit member (5).

[0057] A connection structure (10) according to one embodiment obtained in this way is provided as shown in FIG. 3 (b), a first circuit member (4) having a first electrode (7) installed on a first substrate (6) and a second circuit member (5) having a second electrode (9) installed on a second substrate (8), and a connection part (11) installed between the first circuit member (4) and the second circuit member (5) and electrically connecting the first circuit member (4) (first electrode (7)) and the second circuit member (5) (second electrode (9)) to each other. The connection part (11) is composed of a cured product of an adhesive composition and consists of a cured product (12) of an adhesive component (2) and conductive particles (3) dispersed in the cured product (12). In the connection structure (10), the first electrode (7) and the second electrode (9) are electrically connected to each other by interposing a conductive particle (3) between the first electrode (7) and the second electrode (9).

[0058] The first substrate (6) may be, for example, an IC chip or a flexible substrate. The second substrate (8) may be, for example, a flexible substrate, a glass substrate, or a composite substrate having a glass substrate and an insulating film installed on the glass substrate.

[0059] As a combination of the first substrate (6) and the second substrate (8), more specifically, the first substrate (6) may be an IC chip or a flexible substrate, and the second substrate (8) may be a flexible substrate. Alternatively, the first substrate (6) may be an IC chip or a flexible substrate, and the second substrate (8) may be a glass substrate or a composite substrate. In other words, when the second substrate (8) is a flexible substrate, the first substrate (6) may be an IC chip or a flexible substrate. When the first substrate (6) is an IC chip and the second substrate (8) is a flexible substrate, the adhesive film (1) described above is used for COP (Chip on Plastic substrate) connection. When the first substrate (6) and the second substrate (8) are flexible substrates, the adhesive film (1) described above is used for FOP (Film on Plastic substrate) connection.

[0060] The flexible substrate comprises at least one thermoplastic resin selected from the group consisting of, for example, polyimide (PI), polyethylene terephthalate (PET), polycarbonate (PC), and polyethylene naphthalate (PEN).

[0061] The flexible substrate may further have a modified treatment film, such as a hard coat, and / or a protective film formed on the surface of the organic substrate to improve optical and mechanical properties. To facilitate the handling and transport of the flexible substrate, a reinforcing material selected from glass substrates and SUS, etc., may be bonded to the organic substrate.

[0062] The thickness of the flexible substrate may be 10 μm or more, 200 μm or less, or 125 μm or less, in order to ensure strength and flexibility as a film in the substrate alone.

[0063] The glass substrate may be formed of soda glass, quartz glass, etc., and for the purpose of preventing breakage due to external stress, it may be a substrate that has undergone chemical strengthening treatment. The composite substrate may have a glass substrate and an insulating film composed of polyimide or a coloring organic or inorganic material for decoration installed on the surface of the glass substrate, and in the composite substrate, an electrode may be formed on the insulating film.

[0064] When the second substrate (8) is a flexible substrate, the first substrate (6) may be an electronic component such as a semiconductor chip, active component such as a transistor, diode, thyristor, passive component such as a capacitor, resistor, coil, etc., or a printed circuit board. When the first substrate (6) is an IC chip, a bump formed by plating or the tip of a gold wire may be melted by a torch or the like to form a gold ball, and after pressing this ball onto an electrode pad, a protruding electrode (first electrode (7)) such as a wire bump obtained by cutting the wire may be installed and used as the first circuit member (4).

[0065] The first electrode (7) and the second electrode (9) may be formed of, for example, metals such as Ag, Ni, Al, Au, Cu, Sn, Ti, Mo, or metal oxides such as ITO and IZO. The first electrode (7) and the second electrode (9) may be formed of the same material or different materials. In the first circuit member (4) and the second circuit member (5), the first electrode (7) or the second electrode (9) may each be installed individually, but preferably, multiple electrodes are installed at a predetermined interval.

[0066] At least one of the first electrode (7) and the second electrode (9) has a layer formed of Cu or Ag on the outermost surface of the electrode, and preferably only one of the first electrode (7) and the second electrode (9) has a layer formed of Cu or Ag on the outermost surface of the electrode. In one embodiment, the first electrode (7) may have a layer formed of Sn on the outermost surface of the electrode and the second electrode (9) may have a layer formed of Cu on the outermost surface of the electrode, or the first electrode (7) may have a layer formed of Cu on the outermost surface of the electrode and the second electrode (9) may have a layer formed of ITO on the outermost surface of the electrode, or the first electrode (7) may have a layer formed of Sn or Au on the outermost surface of the electrode and the second electrode (9) may have a layer formed of Ag on the outermost surface of the electrode.

[0067] When using the above circuit connection material (adhesive film), even if at least one of the first electrode (7) and the second electrode (9) has a layer formed of Cu or Ag on the outermost surface of the electrode, a more reliable electrical connection can be obtained.

[0068] [Example]

[0069] The present invention will be explained in more detail below with reference to examples. However, the present invention is not limited to these examples.

[0070] [Example 1]

[0071] Synthesis of Polyurethane Acrylate (UA1)

[0072] 2,500 parts by mass (2.50 mol) of poly(1,6-hexanediol carbonate) (product name: Dulanol T5652, manufactured by Asahi Kasei Chemicals Co., Ltd., number average molecular weight 1,000) and 666 parts by mass (3.0 mol) of isophorone diisocyanate (manufactured by Sigma Aldrich Co., Ltd.) were uniformly dropped over a period of 3 hours into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser with a calcium chloride drying tube, and a nitrogen gas introduction tube. Subsequently, after sufficiently introducing nitrogen gas into the reaction vessel, the inside of the reaction vessel was heated to 70 to 75°C and the reaction was carried out. Next, 0.53 parts by mass (4.3 mmol) of hydroquinone monomethyl ether (Sigma Aldrich) and 5.53 parts by mass (8.8 mmol) of dibutyltin dilaurate (Sigma Aldrich) were added to a reaction vessel, and then 238 parts by mass (2.05 mol) of 2-hydroxyethyl acrylate (Sigma Aldrich) were added and reacted at 70°C for 6 hours under an air atmosphere. As a result, polyurethane acrylate (UA1) was obtained. The weight average molecular weight (Mw) of polyurethane acrylate (UA1) was 15,000. In addition, the weight average molecular weight was measured using a calibration curve based on standard polystyrene rather than gel permeation chromatography (GPC) under the following conditions.

[0073] (Measurement conditions)

[0074] Device: GPC-8020 manufactured by Dosho Kabushiki Kaisha

[0075] Detector: Toso Kabushiki Kaisha RI-8020

[0076] Column: Hitachi Kasei Co., Ltd. Gelpack GLA160S+GLA150S

[0077] Sample concentration: 120 mg / 3 mL

[0078] Solvent: Tetrahydrofuran

[0079] Injection volume: 60μL

[0080] Pressure: 2.94X10 6 Pa(30kgf / cm 2 )

[0081] Flow rate: 1.00 mL / min

[0082] <Production of Conductive Particle 1>

[0083] A layer made of nickel (Ni) with a layer thickness of 100 nm was formed on the surface of polystyrene particles with an average particle size of 5 μm, and a second metal layer made of palladium (Pd) with a layer thickness of 20 nm was further formed on the surface. In this way, an average particle size of 5.2 μm and a specific gravity of 2.2 g / cm³ 3 A conductive particle 1 of ) was obtained.

[0084] <Production of a film-shaped adhesive composition (adhesive film)>

[0085] After mixing each of the following components in the following proportions (parts by mass), the conductive particle 1 described above was added in such a way that it was 5 parts by mass relative to 100 parts by mass of the total mass of the solids (adhesive components) other than the conductive particle of the adhesive composition, thereby obtaining a varnish of the adhesive composition. Subsequently, the varnish of the adhesive composition was applied onto a PET film with a thickness of 50 μm using a coating application device. Then, hot air drying was performed at 70°C for 3 minutes to produce an adhesive film with a thickness of 14 μm on the PET film.

[0086] (Radical polymerizable compound)

[0087] · Bis(acryloxyethyl)isocyanurate (Product name: M-215, manufactured by Doa Kose Co., Ltd.): 15 parts by mass

[0088] · Polyurethane acrylate (UA1) synthesized as described above: 32.5 parts by mass

[0089] · 2-Methacryloyloxyethyl phosphate (Trade name: Light Ester P-2M, manufactured by Kyoei Co., Ltd.): 1.5 parts by mass

[0090] (Radical polymerization initiator)

[0091] · Benzoyl peroxide (Product name: Naiper BMT-K40, manufactured by Nichiyu Corporation): 2.5 parts by mass

[0092] (Thermoplastic resin)

[0093] · Bisphenol A type phenoxy resin (Trade name: PKHC, manufactured by Union Carbide): 42.5 parts by mass

[0094] (Coupling agent)

[0095] · 3-Methacryloxypropyl Trimethoxysilane (Product Name: KBM503, manufactured by Shin-Etsu Chemical Co., Ltd.): 1 part by mass

[0096] (filling)

[0097] · Silica particles (Product name: R104, manufactured by Nippon Aerosil Co., Ltd., average particle size (primary particle size): 12 nm): 5 parts by mass

[0098] (solvent)

[0099] ·Methyl ethyl ketone: 150 parts by mass

[0100] [Example 2]

[0101] An adhesive film was prepared in the same manner as in Example 1, except that conductive particle 2 prepared as described below was used as the conductive particle.

[0102] Production of Conductive Particle 2

[0103] Conductive particle 2 was fabricated in the same manner as conductive particle 1, except that as the second metal layer, a layer made of gold (Au) was formed with a layer thickness of 20 nm instead of a layer made of Pd.

[0104] [Example 3]

[0105] An adhesive film was prepared in the same manner as in Example 1, except that conductive particle 3 prepared as described below was used as the conductive particle.

[0106] Production of Conductive Particle 3

[0107] A layer made of Ni with a layer thickness of 100 nm was formed on the surface of polystyrene particles with an average particle size of 3 μm, and a second metal layer made of Pd with a layer thickness of 20 nm was further formed on the surface. In this way, an average particle size of 3.2 μm and a specific gravity of 2.5 g / cm³ 3 ) obtained conductive particle 3.

[0108] [Example 4]

[0109] An adhesive film was prepared in the same manner as in Example 1, except that conductive particle 4 prepared as described below was used as the conductive particle.

[0110] Production of Conductive Particle 4

[0111] Conductive particle 4 was fabricated in the same manner as conductive particle 3, except that as the second metal layer, a layer made of Au was formed with a layer thickness of 20 nm instead of a layer made of Pd.

[0112] [Comparative Example 1]

[0113] An adhesive film was prepared in the same manner as in Example 1, except that conductive particle 5 prepared as described below was used as the conductive particle.

[0114] Production of Conductive Particle 5

[0115] Conductive particle 5 was produced in the same manner as conductive particle 1, except that a second metal layer was not formed.

[0116] [Comparative Example 2]

[0117] An adhesive film was prepared in the same manner as in Example 1, except that conductive particle 6 prepared as described below was used as the conductive particle.

[0118] Production of Conductive Particle 6

[0119] Conductive particle 6 was produced in the same manner as conductive particle 3, except that a second metal layer was not formed.

[0120] <Creation of Connection Structure>

[0121] Using each adhesive film of the examples and comparative examples, the following connection structures 1 to 5 were fabricated.

[0122] (Connection structure 1 (Electrode outermost surface: Sn / Cu))

[0123] Each adhesive film (with a PET film attached) of the example and comparative example was cut to a size of 1 mm in width and 4 cm in length. Additionally, a circuit member A1 (electrode outermost surface: Cu) was prepared on a glass substrate, with electrodes installed in the order of titanium (film thickness 50 nm) and copper (film thickness 500 nm). Then, the adhesive film on the PET film was transferred onto this circuit member (to cover the electrodes). The transfer conditions were set at 70°C and 1 MPa for 2 seconds. Afterward, the PET film was peeled off to expose the adhesive film, and a flexible circuit member B1 (FPC, electrode outermost surface: Sn) having 150 tin-plated copper circuits with a pitch of 200 μm and a thickness of 8 μm was temporarily fixed on a polyimide substrate to obtain a temporarily fixed structure. The temporary fixation conditions were set at 24°C and 0.5 MPa for 1 second. Next, the temporarily fixed structure was installed in the compression device, a silicone rubber sheet with a thickness of 200 μm was used as a cushioning material, and from the FPC side, it was heated and pressed by a heat tool at 140°C and 2 MPa for 10 seconds to form a connection over a width of 1 mm. By doing so, a connection structure was obtained.

[0124] (Connection structure 2 (Electrode outermost surface: Cu / ITO))

[0125] A connection structure 2 was obtained in the same manner as connection structure 1, except that a circuit member A2 (electrode outermost surface: ITO) having an ITO (film thickness 100 nm) electrode installed on a glass substrate was used instead of circuit member A1, and a flexible circuit member B2 (FPC, electrode outermost surface: Cu) having 150 copper circuits with a pitch of 200 μm and a thickness of 8 μm was used on a polyimide substrate instead of flexible circuit member B1.

[0126] (Connection structure 3 (Electrode outermost surface: Au / Cu))

[0127] A connection structure 3 was obtained in the same manner as connection structure 1, except that a circuit member A3 (electrode outermost surface: Cu) with a Cu (film thickness 500 nm) electrode installed on a PET substrate was used instead of circuit member A1, and a flexible circuit member B3 (FPC, electrode outermost surface: Au) having 150 gold-plated copper circuits with a pitch of 200 μm and a thickness of 12 μm was used on a polyimide substrate instead of flexible circuit member B1.

[0128] (Connection structure 4 (Electrode outermost surface: Au / Ag))

[0129] A connection structure 4 was obtained in the same manner as connection structure 1, except that a circuit member A4 (electrode outermost surface: Ag) with an electrode (film thickness 10 μm) formed of Ag paste on a PET substrate was used instead of circuit member A1, and a flexible circuit member B3 (FPC, electrode outermost surface: Au) was used instead of flexible circuit member B1.

[0130] (Connection structure 5 (Electrode outermost surface: Sn / ITO))

[0131] A connection structure 5 was obtained in the same way as connection structure 1, except that circuit member A2 (electrode outermost surface: ITO) was used instead of circuit member A1.

[0132] <Connection Reliability Assessment>

[0133] Each obtained connection structure was subjected to a reliability test at 85°C, 85% RH, for 500 hours. For the connection structures before and after the test, the connection resistance (Ω) between opposing circuit members was measured. The results are shown in Table 1.

[0134]

[0135] When the outermost surface of the electrode in at least one circuit member is formed of Cu or Ag (connection structures 1 to 4), using an adhesive film (Examples 1 to 4) containing conductive particles 1 to 4 whose outermost surface is formed of Pd or Au resulted in a more reliable electrical connection compared to when an adhesive film (Comparative Examples 1 and 2) containing conductive particles 5 and 6 whose outermost surface is formed of Ni was used. On the other hand, when the outermost surface of the electrode in the circuit member is formed of a metal other than Cu and Ag (connection structure 5), no difference in connection resistance was observed due to the type of the outermost surface of the conductive particles as described above. Explanation of the symbols

[0136] 1: Adhesive film 2: Adhesive components 3: Conductive particles 4: First circuit component 5: Second circuit component 6: First substrate 7: First electrode 8: Second substrate 9: Second electrode 10: Connection structure 11: Connection part 31: Polymer particles 32, 32A, 32B: First metal layer 33, 33A, 33B: Second metal layer 34: Protrusion.

Claims

Claim 1 A connection structure comprising a first circuit member having a first electrode, a second circuit member having a second electrode, and a connecting portion installed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein at least one of the first electrode and the second electrode has a layer formed of Ag on its outermost surface, and the connecting portion has a layer formed of Pd or Au on its outermost surface, wherein the conductive particle comprises a polymer particle, a first metal layer installed on the polymer particle, and a second metal layer installed on the first metal layer, and wherein the thickness of the second metal layer is 2 nm or more and 20 nm or less. Claim 2 A connection structure according to claim 1, wherein the conductive particles have a layer formed of Pd on the outermost surface. Claim 3 An adhesive composition containing an adhesive component and conductive particles, used to electrically connect a first circuit member having a first electrode and a second circuit member having a second electrode by bonding them together, wherein the conductive particles have a layer formed of Pd or Au on their outermost surface, the conductive particles have a polymer particle, a first metal layer installed on the polymer particle, and a second metal layer installed on the first metal layer, wherein the thickness of the second metal layer is 2 nm or more and 20 nm or less, and at least one of the first electrode and the second electrode has a layer formed of Ag on its outermost surface. Claim 4 An adhesive composition according to claim 3, wherein the conductive particles have a layer formed of Pd on their outermost surface.

Citation Information

Patent Citations

  • Plasma display device

    JP2007094412A

  • Anisotropic conductive material, connection structure and method for producing connection structure

    JP2013149774A

  • Circuit connection material, circuit connection material structure and manufacturing method of circuit connection material structure

    JP2013214417A